Chagas disease in dogs from endemic areas of Costa Rica - Zeledón, Rodrigo (2002)
Dogs with the presumptive diagnosis of Chagas disease are commonly sent to our School of Veterinary Medicine by independent veterinarians. This prompted us to evaluate the prevalence of canine trypanosomiasis in some villages of the Central Valley of Costa Rica. A total of 54 dogs (21 males and 33 females) from five rural villages, with ages between 3 months and 10 years old, were bled and submitted to three serological tests: indirect iminunofluorescence, indirect hemagglutination and ELISA. Among all animals. 15 (27.7%) revealed antibodies (6 pure bred and 9 mongrels) and in 3 of them the parasite was also demonstrated by xenodiagnosis. All positive animals except 1. and 9 negative animals (control group) were examined by X-rays and electrocardiography, revealing different degrees of cardiomegaly and ECG alteration, consistent with Chagas disease pathology in one dog (SA-11) of the infected ones. Examination of 50 inhabitants living in the houses where dogs and Triatoma dimidiata were found, yielded negative serological reactions. This was assumed to support the hypothesis that dogs are commonly infected by the oral route, a more effective means of infection compared with the vector transmission mechanism that occurs in humans.